The shoemaker's wife [compact disc, unabridged] : a novel - Trigiani, Adriana (Harperaudio, 2012)
Two star-crossed lovers--Enzo and Ciro--meet and separate, until, finally, the power of their love changes both of their lives forever. Set during the years preceding and during World War I.